A systematic literature review on the use of podcasts in education among university students - Amirul Zulaidil Shah Ahmad Shahrizal; Bahbibi Rahmatullah; Mad Helmi Ab Majid; Suzani Mohamad Samuri; Hidayanto, Achmad Nizar; M. Yas, Qahtan; Purnama, Sigit (Penerbit Universiti Kebangsaan Malaysia, 2022)
Technology such as multimedia, particularly podcasts, is becoming more widely used in educational settings. The podcasts have been utilized at many levels of education, including elementary, secondary, and tertiary education. Along with this, many articles were written and published about the use of podcasts in education among university students. Our main objective in this study is to examine the use of podcasts in higher education among university students by systematically searching the Scopus database for papers relevant to the study. Eighteen papers were chosen and retrieved, then meticulously studied to uncover the new themes that have been classified as the result. The review found that podcasts have a favorable impact on university students and help them better understand the learning process. It also highlights the limits in its deployment that need to be addressed in order to improve the teaching and learning process.